Effects of Collaborative and Non-Collaborative Approaches to Teaching Reading Strategies on Iranian efl Learners’ Reading Comprehension and Attitude toward Reading - Rajaei, Azadeh; Talebi, Seyed Hassan; Abadikhah, Shirin (Íkala, Revista de Lenguaje y Cultura, 2020)
In an EFL context reading is a very important skill in language learning. This study aims at finding if instruction of reading strategies in two different collaborative and non-collaborative approaches affects reading comprehension and attitude toward reading differently. Forty-five Iranian adult female EFL learners at pre-intermediate general English proficiency level in Iran Language Institute (ili) were selected and divided into three groups of 15 students. One group functioning as the control group did not receive any strategy instruction; the second group, as the first experimental group, received reading strategy instruction in collaborative groups (Collaborative Strategic Reading or csr), and the third group considered as the second experimental group received reading strategy instruction in a non-collaborative way. A reading comprehension test and a reading attitude questionnaire were given to all three groups at the beginning of the term as pretests and after the experiment as posttests. The results obtained through one-way anova indicated that though both experimental groups outperformed the control group, there was no significant difference between the two experimental groups in reading comprehension and attitude toward reading. Therefore, it is up to teachers to weigh the advantages of using the collaborative approach to teaching reading against its disadvantages.